Gypsy boy on the run - Walsh, Mikey (Hodder, 2011)
Mikey was born into a Romany Gypsy family. They lived in a closeted community, and little is known of their way of life. After centuries of persecution Gypsies are wary of outsiders and if you choose to leave you can never come back. This is something Mikey knows all too well. Growing up, he didn't go to school, he seldom mixed with non-Gypsies and the caravan became his world. Eventually Mikey was forced to make an agonising decision - to stay and keep secrets, or escape to find somewhere to belong.